The election of Israel : the idea of the chosen people - Novak, David, 1941- (Cambridge [England] ; New York, NY, USA : Cambridge University Press, 1995)
In this book, David Novak conducts a historical, philosophical, and theological reflection on the central Jewish doctrine of Israel's election by God, also known as the idea of the chosen people. historically, he analyzes the great change in modern jewish thought brought about by Spinoza's inversion of the doctrine: that it was not god, who elected Israel, but Israel who elected god.
Spinoza and his challenge -- Hermann Cohen's concept of election -- Franz Rosenzweig's return to the doctrine -- The retrieval of the biblical doctrine -- The rabbinic development of the doctrine -- Two medieval views of election.
Includes bibliographical references (p. 266-277) and index.
Keywords: Jews -- Election, Doctrine of -- History of doctrines; Jews -- Identity